Hematological Analysis of Nile Tilapia (Oreochromis niloticus) and Striped Catfish (Pangasius hypophthalmus) using Hematology Analyzer Tool Software at Fish Breeding Center Jojogan, Tuban, East Java - Maftuch Maftuch (Research Journal of Life Science, 2018)
Nile tilapia and Striped Catfish can be classified as freshwater fish species that have great cultivation potential. Inadequate cultivation management leads to the occurrence of disease attacks on fish. Hematological examination was applied to determine the level of fish health. This research was aimed to know the difference between erythrocyte cell and leucocyte cell count by using Hematology Analyzer Tool Software (computer based) and hand tally counter (human based), and to know the description of hematocrit component, hemoglobin and leucocytes differential on tilapia fish and Striped Catfish. The methods employed in this research were experimental method and descriptive method. The results showed that the calculation of erythrocyte cells and leucocyte cells by using Hematology Analyzer Tool Software was similar to the calculation by using hand tally counter. It was because the result of t value was smaller than t of the 5% table. Based on the description of the hematocrit component, hemoglobin and leucocyte differentials, it could be said that nile tilapia and Striped Catfish were within the range of abnormalities.